FASHION EVOLUTION IN EMERGING CONTEXTS AND THE ROLE OF CREATIVE CENTERS - Doina NISTOR (Economica, 2024)
The article explores the impact of the fashion design center ZIPhouse on the evolution of the fashion industry in the Republic of Moldova, highlighting the transition from manu- facturing to design and own brands. The light industry in the Republic of Moldova has demon- strated resilience and growth, especially in exports, but it requires transitioning to more innovative models and focusing on design and own brands to remain competitive in the long term and overcome challenges related to high costs and declining workforce. The strategic development of creative hubs, such as ZIPhouse, is essential for supporting innovation and sus- tainable growth in the fashion industry. Colla- boration between universities and industry, as well as the integration of digital technologies, plays a crucial role in advancing skills and businesses in this sector. The article emphasizes ZIPhouse’s contributions to sustainable fashion education and the fashion ecosystem in the Republic of Moldova, highlighting community development and international collaboration.